2014
DOI: 10.1080/14660970.2014.882822
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s like equality now; it’s not as if it’s the old days’: an investigation into gender identity development and football participation of adolescent girls

Abstract: This article explores the influence participating in football has on the development of adolescent girls’ gender identity, an area which currently lacks academic attention. Data were taken from an ethnographic study with a group of adolescent girls and boys and compared to Jeanes’ research. A social constructionist framework was deployed with links to both critical theory and feminist literature. Qualitative and participatory methods were used to fully engage with the complex issue of gender identity. The girl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For example, Swain (2000) and Clark and Paechter (2007) highlight how girls' access to informal football opportunities at school are limited by the spatial monopolisation of playgrounds by young boys. Jeans and Kay (2007), Jeanes (2011), andPielichaty (2015) work explores young girls' experiences of negotiating the contradictions between "feminine" and footballer identities. Similar themes are explored amongst adult women footballers by Welford and Kay (2007) and Themen (2016), who uncover the tensions that arise between normative notions of femininity and the physicality required for football prowess.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Swain (2000) and Clark and Paechter (2007) highlight how girls' access to informal football opportunities at school are limited by the spatial monopolisation of playgrounds by young boys. Jeans and Kay (2007), Jeanes (2011), andPielichaty (2015) work explores young girls' experiences of negotiating the contradictions between "feminine" and footballer identities. Similar themes are explored amongst adult women footballers by Welford and Kay (2007) and Themen (2016), who uncover the tensions that arise between normative notions of femininity and the physicality required for football prowess.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is widely documented that women's football has experienced a surge in popularity over the past 20 years (Pielichaty, 2015;Bell, 2019;Clarkson et al, 2020). The development of the Women's Super League (WSL) in England and increased media coverage of global competitions has gone some way toward recognising elite women players in popular culture (Woodhouse et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Players have reportedly enjoyed being competitive, aggressive, skilful and determined (Scraton et al, 1999) and have felt able to ‘let go of gender role expectations and do what they love doing, namely playing soccer’ (Grundlingh, 2010: 52). Furthermore, Pielichaty’s previous study demonstrated that soccer was utilized as a platform for girls to prove ‘the boys’ wrong as well as describing the sport as ‘relaxing, energetic, a chance to tackle people and take your anger out on something’ (2015: 498). Cox and Pringle’s paper reports on ‘specific footballing pleasures’ (2011: 229) and the transformative power of pleasure to help players tackle inequality and contribute to sustained participation.…”
Section: Girls’ and Women’s Soccer Culture: Progress Or Hyperbole?mentioning
confidence: 99%
“…The internalisation of the norms and values are often a prerequisite for acceptance at inter-personal, institutional and community levels. Pielichaty (2015) refers to creating a "web-of-selves" with reference to how girls present different versions of themselves according to circumstances and relationships, which they negotiate for personal gain. The traditional and contemporary South African society is ideologically positioned by patriarchy.…”
Section: Barriers Limitations and Opportunities Barriers And Limitationsmentioning
confidence: 99%